Regional Specifics of Using Community Bins in Waste Management: a Case Study of Rural Communities in Poltava Region (Ukraine) - Viktor Bredun; Rakesh Choudhary; Ajay Kumar (Trends in Ecological and Indoor Environmental Engineering)
Background: The growing waste amount generation and its negative impact on the environment have become a serious problem. Many regions of Ukraine are not ready for modern challenges in the field of municipal solid waste (MSW) management. Inadequate waste management strategies at the regional level, taking into account local technical and economic features, require the attention of researchers. In particular, the technological component of local and regional MSW management systems in rural communities of the Poltava region (Ukraine) needs to be analysed and modernized, as well as the development of a technology for the use of specialized community bins to ensure environmental safety and efficient waste management